Analysis of Effect of Power Distance, Power Avoidance, Individualism, Masculinity and Time Orientation Toward Auditing Behavior with Mediation of Locus of Control - Limajatini Limajatini; Etty Murwaningsari; Khomsiyah Khomsiyah (Komunitas Dosen Indonesia, 2019)
The occurrence of financial scandals have been concerned by many public accountants to provide more ethical awareness to work ethically. In the task of auditing, public accountants are often faced with ethical dilemmas caused auditing conflict. This study focused on the effect of locus of control and how public accountants and auditors aware the effect toward their auditing behavior. We used causal and descriptive research design to measure the effects of cultural, ethical behavior among accountants and auditors with moderation of locus of control. Our study results showed that, firstly, power distance between the auditors and accountants will affect their ethical behavior in the work. Secondly, the avoidance of uncertainty among the auditors will affect their ethical behavior toward accountants. Thirdly, the attitude of individualism among the auditors and accountants also will affect their ethical behavior in auditing tasks. The attitude of masculinity also impacted on their ethical behavior to fulfill the auditing tasks. Time orientation has more significant result which impacting their ethical behavior. Finally, Locus of control can strengthening the power distance and ethical conduct among accountants and auditors. This study contributed to expand the auditing knowledge and the factors that impact on their ethical behavior in auditing tasks.